Using The Autoregressive Distributed Lag Period (ARDL) Model To Study The Impact Of Some Economic Variables On The Inflation Rate In Syria During The Period 2000-2022 - نصره زين العابدين; عز الدين حيدر (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aims to analyze the reality of the phenomenon of inflation in Syria and measure the impact of inflation on some economic variables (the exchange rate, GDP at current prices, GDP at constant prices, average total annual household consumption expenditure and unemployment rate) in Syria during the period 2000-2022 using simple linear regression and analyzed using spss. The research found a weak direct relationship between the inflation rate and the exchange rate, a weak direct relationship between the inflation rate and GDP at current prices, a weak inverse relationship between the inflation rate and GDP at constant prices, and a weak direct relationship between the inflation rate and average consumer spending. The annual total of the family, and there is a weak direct relationship between the rate of inflation and the rate of unemployment and was the most influential.